The Implementation of Instructional Games Model Using Quizizz Application in Improving Students’ Vocabulary - Dian, Vonny; Said, Riani (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
The objective of the research is to find out whether or not the implementation of the Instructional Games Model using the ‘Quizizz’ application has a significant effect on the students’ vocabulary at SMK 1 Bone. The method of this research was a pre-experimental method with one group pre-test and post-test and this method tends to see the results of the research where is there any improvement in students’ vocabulary after implementing the instructional games model using the Quizizz application. The instrument of the research was a vocabulary test that was given as a pre-test and a post-test. In the end, this research shows that there was an improvement made by the tenth-grade students. This is proven by the students’ mean score from the pre-test which was 56.6 and the improvement increased by 88.9 from the post-test. The observation results showed that the Implementation of the Instructional Games Model Using Quizizz Application could improve the students’ vocabulary. So, from this research, it can be concluded that the Implementation of the Instructional Games Model Using the Quizizz Application could improve the student’s vocabulary in the class of PN 4 at SMK 1 Bone.